Outcome and predictive value of variables in the inpatient treatment of anorexia nervosa at the eating disorders unit, Tara the H Moross Hospital - Abrie, Anina (My University, 2013)
Eating disorders can be considered to be severe chronic mental illnesses as anorexia nervosa has a standard mortality rate of 0-17.8. Outcome definition in the short and long term is not standardised. Although many treatments are described, there is no clear data on the optimal treatment for anorexia nervosa. Various studies have investigated predictors of successful outcome, in the short and long term management of the disorder. The current study aimed to investigate outcome in the short term, i.e. weight restoration to within 95% of a BMI of 18.5, as suggested by Couturier and Lock. The predictive value of variables measured on admission to the eating disorders unit of TARA the HR Moross Hospital, as it relates to the short term outcome of the inpatient treatment provided, were examined. The results indicate a high level of chronicity in the female cohort of 42 patients admitted to the program, as 85.7% of the patients previously had treatment for anorexia nervosa, and seven of the patients were readmitted in the study period. A genetic factor, or shared environmental factors might be involved as 28.3% of first and second degree relatives also had past treatment for anorexia nervosa. A high level of co-morbidity was found. Average length of stay was 90.8 days (SD 39.6). Average admission BMI was 14.2 (SD 1.20) and average discharge BMI was 16.5 (SD 2.97), i.e. an average weight change per patient of 2.3 BMI units (SD 1.77). The outcome as measured on Couturier and Lock’s criterion of ≥95% of desired BMI (18.5) was an average of -3.11 kg (SD 7.56) per patient. Whilst the outcome did not reach the set criterion, most patients gained weight on the programme, with four patients maintaining their weight at the same level, and one patient losing 3.7 kg. The mean gain per patient was 6.16 kg (SD 4.596) over the admission period, indicating benefit to the majority of the patients. Non-completion of the programme and readmission to the programme were associated with poor weight gain. Non-completers were more likely than completers to be scholars (unemployed versus being a scholar; OR=2.91; employed versus being a scholar; OR=19.2), past substance abuse (OR=3.14), being non-Caucasian (OR=0.59), and the personality variables passivity (OR=2.5), dependency (OR=2.92), mood stability (OR=0.19), considering consequences of actions (OR=0.20). The small sample size of 12 of the 49 data sets of non-Caucasian users precluded meaningful statistical analysis. Non-Caucasians differed from Caucasians with 92% non-Caucasians versus 59% Caucasians classified as the restricting subtype. Non-Caucasians had fewer mood swings (43% versus 71%), less self-destructiveness (14% versus 56%), lower impulsivity (11% versus 40%) and a lower occurrence of an external locus of control (11% versus 41%), than Caucasians. More scholars were non-Caucasian (50% versus 41%). Differences in home language and religion could be ascribed to selection bias in the small sample set.
Keywords: Anorexia Nervosa